T cell exhaustion is associated with antigen abundance and promotes transplant acceptance. Issue 9 (17th April 2020) - Zou, Dawei; Dai, Yulin; Zhang, Xiaolong; Wang, Guohua; Xiao, Xiang; Jia, Peilin; Li, Xian C.; Guo, Zhiyong; Chen, Wenhao
Abstract : Exhaustion of T cells limits their ability to clear chronic infections or eradicate tumors. Here, in the context of transplant, we investigated whether T cell exhaustion occurs and has a role in determining transplant outcome. A peptide/MHC tetramer‐based approach was used to track exhausted CD8 + T cells in a male‐to‐female skin transplant model. Transplant of large whole‐tail skins, but not small tail skins (0.8 cm × 0.8 cm), led to exhaustion of anti‐male tetramer + CD8 + T cells and subsequently the acceptance of skin grafts. To study CD4 + T cell exhaustion, we used the TCR‐transgenic B6 TEa cells that recognize a major transplant antigen I‐Eα from Balb/c mice. TEa cells were adoptively transferred either into B6 recipients that received Balb/c donor skins or into CB6F1 mice that contained an excessive amount of I‐Eα antigen. Adoptively transferred TEa cells in skin‐graft recipients were not exhausted. By contrast, virtually all adoptively transferred TEa cells were exhausted in CB6F1 mice. Those exhausted TEa cells lost ability to reject Balb/c skins upon further transfer into lymphopenic B6. Rag1 −/− mice. Hence, T cell exhaustion develops in the presence of abundant antigen and promotes transplant acceptance. These findings are essential for better understanding the nature of transplant tolerance. Abstract : Zou et al demonstrate in a mouse model that T cell exhaustion depends upon antigen load, measured by skin graft size, and promotes transplant acceptance. See Ford's editorial on page 2303 .